Creating Josaphat: The Making of a Saint in the Church-Slavonic Office for Josaphat Kuntsevych - Takala-Roszczenko, Maria (Lietuvos istorijos studijos, 2025)
The liturgical commemoration of Josaphat Kuntsevych, the Uniate Archbishop of Polatsk, was initiated soon after his death in the hands of Orthodox citizens in Vitsyebsk in 1623. The hymnographical Office (sluzhba) for Josaphat developed in the course of the seventeenth century, first in manuscripts, and, from the 1730s, at the latest, also in the printed form. This article examines the Office with a constructivist approach, analyzing how the historical figure is turned into a hymnographical protagonist through the selection of relevant elements and life events that demonstrate his sanctity. The focus is on three aspects: the ‘saintly arguments’ that are used in ‘creating Josaphat’, the imitation of Christ through parallel narratives, and the depiction of Josaphat as the pillar of the Church Union.